Analisis Motivasi Kerja pada Pegawai Kelurahan Xyz di Jakarta Selatan - Surti Wardani; Rika Parwati (Syntax Idea)
This research aims to analyse employee’s motivation at XYZ sub-district office in South Jakarta. The method used is descriptive qualitative, that analysed the data based on reality, then connected to the theory that supports the discussion, then the author draws conclusions from the explanation. The social situation consists of place, actors, and activity in Kelurahan XYZ Office. All the employee were the actors as the main source of information in the research. Data collection techniques used primary data sources from interviews, observations, documentation studies, library research, and secondary data sources consisting of general company data, personnel data, organizational structures and charts. The data analysis technique used the theory of Miles consist of data collection, data reduction, data presentation, drawing conclusions and also using source triangulation techniques to develop the validity of the data obtained. The results shown, the employee motivation at Kelurahan XYZ was good and needed to be increased, the efforts made in providing motivation to employees have met standards and still needed strengthening, and several factors founded that became obstacles in providing motivation such as; the lack of human resources, and it was found that on the average employees are approaching retirement age. Overall, motivation can lead to employee productivity in the future. This can be done through increasing and strengthening employee motivation, and minimizing or eliminating the inhibiting factors in the implementation of providing employee motivation.